Implementasi Supervisi Akademik Berbasis Pengelolaan Kinerja dalam Penguatan Manajemen Kelas di SMP Negeri 1 Kemangkon - Handayani, Sa’diyah; Hanif, Muh.; Kharisoh, Umi; Muhdi, Ali; Winarsih, Sri (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the implementation of academic supervision based on Performance Management in strengthening classroom management at SMP Negeri 1 Kemangkon. The study employs a qualitative approach using a case study design. Data were collected through interviews, observations, and documentation involving the principal, supervisors, and supervised teachers. Data analysis was conducted using the Miles, Huberman, and Saldana interactive model through data condensation, data presentation, and drawing conclusions. The results of the study indicate that academic supervision is conducted on a scheduled basis once every semester, involving 10 supervisors and 37 teachers. The implementation of supervision is supported by the Performance Management feature on the guru.kemendikdasmen.go.id platform, which facilitates observation planning, observation implementation, reflection, and follow-up. All teachers chose to focus their performance practices on the instructional aspect of learning. Reflection results indicate the need to strengthen the clarity of instructions, manage learning time, increase student participation, and develop more contextual learning strategies. Follow-up is carried out through the development of self-directed competencies, peer collaboration, and improvements in teaching practices. The implementation of academic supervision based on Performance Management fosters a culture of teacher reflection that contributes to strengthening classroom management and the quality of learning. This is supported by the results of the Academic Ability Test (TKA) at SMP Negeri 1 Kemangkon, which ranked 10th out of 77 schools in Purbalingga Regency. This study concludes that performance management-based academic supervision is an effective means of professional development for teachers in fostering continuous reflection and strengthening classroom management to support the quality of learning.